Pendekatan STEAM dengan Model Inquiry Learning Berbantuan Liveworksheet untuk Meningkatkan Literasi Matematis Siswa SD Kelas V - Wahyuni, Nur Ardiyanti; Rusnilawati, Rusnilawati (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2024)
This research aims to determine the increase in mathematical literacy in students by using the steam approach with a live worksheet based inquiry learning model. This research was carried out at SD N Trosemi 2 in the odd semester of the 2023/2024 academic year with a total of 29 students. This research was conducted in two cycles. The data collection methods in this research are test and observation. Data analysis techniques using qualitative data are based on increasing the average mathematical literacy ability of students as an indicator of research success. The results of research in the pre-cycle showed that the average mathematical literacy of students was 49.54% with poor criteria, in cycle I there was an increase, namely getting an average of 65.5% with good criteria and in cycle II getting an average of 86. 45% with very good criteria. Thus, it can be concluded that using the inquiry learning model assisted by live worksheets using the Steam approach can increase mathematical literacy in students.